Islamic Geometries: Spiritual Affects Against a Secularist Grid - Shaw, Wendy M. K. (Sophia, 2022)
Discussions of surface pattern in Islamic art resonate within broader tensions about the role of figural representation in communicating meaning. The question of whether geometric pattern communicates—whether it functions as a language without a code—reflects broader tensions about the relationship between secular and spiritual communication. Poised between discussions of modernism and Islam, the attribution of linguistic capacity to geometry serves as a measure for the possibility of abstracting pure reason from the religious roots of representationalism. This paper explores this question in four parts. First, it examines the articulation of geometric meaning in Islamic discourses. It then explores European discussions of geometry between language and ornament poised between a search for universal reason and universal spiritualism, both in modernist painting and in modern exhibitions. The final section the expressive capacity of artistic responses to historical Islamic isometric geometries in the adaptive reuse of historical Iranian arts as contemporary abstraction in the sculptures of Monir Shahroudy Farmanfarmaian (1928–1919) and in the popular transformation prints of M. C. Escher (1898–1972). It argues that the frequent recognition of intrinsic meaning in geometry, expressed in both premodern Islamic and modern secular interpretations, undermines art historical expectations of theorization as a necessary intermediary for communication. Geometry thereby functions as a language without a code.